A self-crosslinking high-performance flame-retardant cable

By using self-supply water-type silane coupling agent and modified reactive flame retardant in the cable, the problems of flammability and poor dispersion of flame retardant in traditional cables are solved, and high-performance, long-term and stable flame retardant cable preparation is achieved.

CN118755188BActive Publication Date: 2025-02-14GUANGDONG AOTONG SPECIAL CABLE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411253095.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-14
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

Traditional cables are prone to burning and produce toxic fumes when encountering fire, and the flame retardant of existing crosslinked polyethylene cables has poor dispersion, which affects material performance.

Method used

The self-crosslinking of silanes was performed using a self-supply silane coupling agent, and the DOPO was modified to obtain a reactive flame retardant, which significantly improved the dispersion and interface binding through grafting reaction.

Benefits of technology

The preparation of high-performance flame retardant cables is achieved, with good long-term stability, little impact on mechanical properties, and no additional water supply agent is required, which reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118755188B_ABST
    Figure CN118755188B_ABST
Patent Text Reader

Abstract

The invention discloses a self-crosslinking high-performance flame-retardant cable, which is composed of an insulating core and a flame-retardant protective sleeve. The flame-retardant protective sleeve comprises, by weight, 45-55 parts of linear low-density polyethylene, 15-25 parts of ethylene-octene elastomer, 1.8-2.2 parts of a self-watering silane coupling agent, 10-16 parts of a flame retardant, 4-8 parts of a reactive flame retardant, 0.18-0.22 parts of an initiator, 0.5-0.8 parts of an antioxidant, and 1.6-2.2 parts of a catalyst. When the self-watering silane coupling agent is crosslinked with polyethylene, an amide structure in the structure is closed at high temperature to generate an imide structure and a molecule of water, so as to supply water for internal crosslinking of the polyethylene. The reactive flame retardant can be grafted onto the polyethylene main chain during the crosslinking process, is not easy to migrate, and has a long-term stable flame retardant effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cables, in particular to a self-crosslinking high-performance flame-retardant cable. Background Art

[0002] As an important part of the power and communication system, the performance of cables directly affects the safety and reliability of the entire system. With the development of social economy, the requirements for cables are getting higher and higher, especially in terms of flame retardancy. Traditional cables are easy to burn and produce toxic smoke when exposed to fire, posing a major safety hazard.

[0003] Polyethylene has good processing properties, mechanical properties and dielectric properties, and stands out among many polymers as a cable material. With the development of cross-linked polyethylene technology, cross-linked polyethylene cables have gradually been widely used in power systems due to their excellent mechanical and electrical properties and simple manufacturing process. When manufacturing traditional silane cross-linked polyethylene, the cable material needs to be soaked in warm water or steam, which makes it impossible to use flame retardants and antioxidants that are sensitive to high temperature and high humidity. Silane self-cross-linking polyethylene is a method in which a water supply agent is added during preparation to perform silane cross-linking by internal water supply. This method has low energy consumption and does not require high-temperature cooking. The commonly used water supply agent is a mixture of zinc oxide and organic acid. Both have poor compatibility and dispersibility with cross-linked polyethylene. Excessive addition will inevitably affect the performance of the material.

[0004] At present, the commonly used flame retardants for cross-linked polyethylene include ammonium polyphosphate (APP) and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). Among them, APP has poor dispersibility and often requires a higher addition amount, which will have a certain impact on the mechanical properties of the material, and its thermal stability is not as good as DOPO. If the temperature during the processing of cross-linked polyethylene is too high, it will cause a certain decomposition. DOPO has excellent gas phase flame retardancy and thermal stability, and often only needs to be added in a lower amount to make the material achieve a good flame retardant effect, but its compatibility with cross-linked polyethylene is also poor. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the present invention adopts a self-water-supply silane coupling agent to obtain silane self-crosslinking polyethylene, without the need to add other water-supply agents, and modifies DOPO to obtain a reactive flame retardant. In the step of preparing cross-linked polyethylene, a grafting reaction is carried out with polyethylene, which significantly improves the dispersibility and interface bonding.

[0006] The technical solution of the purpose of the present invention is as follows: a self-crosslinking high-performance flame-retardant cable, consisting of an insulating core and a flame-retardant protective sheath, characterized in that the flame-retardant protective sheath comprises, by weight: 45 to 55 parts of linear low-density polyethylene, 15 to 25 parts of ethylene-octene elastomer, 1.8 to 2.2 parts of self-watering type silane coupling agent, 10 to 16 parts of flame retardant, 4 to 8 parts of reactive flame retardant, 0.18 to 0.22 parts of initiator, 0.5 to 0.8 parts of antioxidant, and 1.6 to 2.2 parts of catalyst.

[0007] The self-water-supply type silane coupling agent is prepared by the following method:

[0008] Under a nitrogen atmosphere, 1.1-1.3 eq of itaconic anhydride was added to the reactor and dissolved in chloroform. After adding 2.5-3.0 eq of amine catalyst, 1.0 eq of silane coupling agent was added to the reactor at 25-35 °C and reacted for 8-16 h. The reaction was stopped, and the mixture was washed three times with aqueous sodium hydroxide solution and three times with saturated ammonium chloride solution. The organic phase was collected and evaporated to obtain a self-water-supplying silane coupling agent.

[0009] The reactive flame retardant is prepared by the following method:

[0010] S1. Synthesis of imide: In a reaction kettle, add 1.0-1.2 eq of hydroxylamine compound and 2.0-2.5 eq of urea, stir at 75-85 °C for 1-2 h, then add 1.5-1.8 eq of itaconic anhydride and 1.5-1.8 eq of urea under nitrogen atmosphere, stir at 135-145 °C for 1-2 h, cool to room temperature after the reaction, add deionized water to produce a white precipitate, collect the solid by filtration, wash with deionized water 3 times, and dry to obtain imide;

[0011] S2. Synthesis of reactive flame retardant: dissolve the imide, halogenating agent and activating agent obtained in S1 with a solvent, stir for 1 to 5 min at 0 to 25°C, slowly add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue stirring for 2 to 30 min, filter to obtain a solid and a filtrate, and wash the solid three times with a solvent during the filtration process, then spin-dry the filtrate to remove the solvent to obtain a solid product, dissolve the product in dichloromethane, wash three times with an aqueous sodium hydroxide solution and an aqueous hydrochloric acid solution in sequence, collect the organic phase, and spin-dry again to obtain a reactive flame retardant.

[0012] In the washing step involved in step S2 of the present invention, the volume ratio of the washing solvent to the washing liquid is 1:5, wherein the washing solvent is a sodium hydroxide aqueous solution and a hydrochloric acid aqueous solution, and the washing liquid is an organic solvent.

[0013] The concentrations of the sodium hydroxide aqueous solution and the hydrochloric acid aqueous solution used in step S2 are 1-2 mol / L.

[0014] Preferably, the flame retardant is expandable graphite; the initiator is dicumyl peroxide; and the catalyst is dibutyltin dilaurate.

[0015] Preferably, the amine catalyst is at least one of triethylamine and N,N-diisopropylethylamine; and the silane coupling agent is at least one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane.

[0016] More preferably, the amine catalyst is triethylamine; and the silane coupling agent is 3-aminopropyltriethoxysilane.

[0017] Preferably, the hydroxylamine compound is at least one of choline chloride and choline bromide.

[0018] More preferably, the hydroxylamine compound is choline chloride.

[0019] Preferably, the halogenating agent is one or more of N-chlorosuccinimide, N-bromosuccinimide, N-iodosuccinimide and dibromohydantoin.

[0020] More preferably, the halogenating agent is N-bromosuccinimide.

[0021] Preferably, the activator is one or more of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,5-diazabicyclo[4.3.0]non-5-ene, triethylenediamine, triethylamine, triphenylphosphine and 1,8-diazabicyclo[5.4.0]undec-7-ene.

[0022] More preferably, the activating agent is 1,8-diazabicyclo[5.4.0]undec-7-ene.

[0023] Preferably, the solvent is one or more of N,N-dimethylformamide, tetrahydrofuran, toluene, dichloromethane and acetonitrile.

[0024] More preferably, the solvent is acetonitrile.

[0025] Preferably, the mass ratio of the flame retardant to the reactive flame retardant is (2-3):1.

[0026] The present invention also protects a method for preparing the self-crosslinking high-performance flame-retardant cable, comprising the following steps:

[0027] 1) Dissolve the initiator in the self-water-supply silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into two equal parts, one part is mixed with the initiator, the self-water-supply silane coupling agent, the flame retardant and the reactive flame retardant, and the other part is mixed with the antioxidant and the catalyst, and put them into sealed containers respectively and let them stand for 18-24 hours, and extrude them respectively with a twin-screw extruder in turn to obtain mixed masterbatch;

[0028] 2) Add the mixed masterbatch into the preheated single screw extruder, extrude the material onto the insulating core, cool it in a water bath, place the obtained material in a humid environment at room temperature for 2 to 3 days, complete the self-crosslinking process of polyethylene, and then dry it to obtain a self-crosslinking high-performance flame-retardant cable.

[0029] Beneficial Effects

[0030] The present invention has the following beneficial effects:

[0031] (1) The use of self-watering silane coupling agent eliminates the need to add other water-supplying agents, thus reducing the impact of other components on material properties; the self-watering silane coupling agent can be grafted onto the polyethylene main chain, without the problem of poor compatibility and dispersibility; by closing the ring to form an imide structure and produce a molecular water, the supplied water can directly react with the siloxane bond to be hydrolyzed, reducing the time spent on the migration of water molecules in polyethylene and accelerating the speed of cross-linking.

[0032] (2) The DOPO structure is modified by the imide structure, and an unsaturated double bond structure is introduced. It can be grafted onto the polyethylene main chain, is not easy to migrate or volatilize, and has a long-term stable flame retardant effect. A smaller amount can be added to achieve a good effect; it becomes a part of the polymer structure, has little negative impact on the mechanical properties, and does not significantly change the processing characteristics of the polymer; the imide structure is introduced to form a nitrogen-phosphorus synergistic flame retardant effect. The phosphoric acid produced by the decomposition of phosphate ester at high temperature reacts with imide to form ammonium phosphate-like substances, which can promote the carbonization of expanded graphite. The generated ammonium phosphate further decomposes with the increase of temperature to release ammonia, converting the carbon layer into an expanded carbon layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the synthesis step of the self-water supply type silane coupling agent and the reactive flame retardant of the present invention;

[0034] Figure 2 It is the self-water supply type silane coupling agent grafting, reactive flame retardant grafting and water supply mechanism of the present invention;

[0035] Figure 3 This is the nuclear magnetic hydrogen spectrum of the self-water supply type silane coupling agent of the present invention;

[0036] Figure 4This is the nuclear magnetic hydrogen spectrum of the reactive flame retardant of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0039] The raw materials and equipment used in the embodiments and comparative examples are described as follows:

[0040] Linear low-density polyethylene: brand DFDA-7042, purchased from Wuhan Rongchuang Plastic Co., Ltd.;

[0041] Ethylene-octene elastomer: brand 8999, purchased from Dongguan Yucheng Plastic Chemical Co., Ltd.;

[0042] Flame retardant: expanded graphite, 60 mesh, Henan Liugong Graphite Co., Ltd.;

[0043] Initiator: dicumyl peroxide, purchased from Tianjin Chemical Reagent Factory No. 1;

[0044] Antioxidant: Antioxidant 1010, purchased from Dongguan Guangsiyuan Polyurethane Materials Co., Ltd.;

[0045] Catalyst: Product No. 2022062710, purchased from Tesco Chemical Co., Ltd.;

[0046] Itaconic anhydride: product number I799098, purchased from Shanghai MacLean Biochemical Technology;

[0047] Silane coupling agent: product number A800523, purchased from Shanghai MacLean Biochemical Technology;

[0048] Hydroxylamine compound: product number C805029, purchased from Shanghai MacLean Biochemical Technology;

[0049] Urea: Product No. U820349, purchased from Shanghai MacLean Biochemical Technology;

[0050] Halogenating agent: Product No. N802275, Shanghai MacLean Biochemical Technology;

[0051] Activator: Product No. D807027, Shanghai MacLean Biochemical Technology;

[0052] 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO): product number D806521, Shanghai MacLean Biochemical Technology;

[0053] Self-watering silane coupling agent

[0054] Under nitrogen atmosphere, 1.3 eq of itaconic anhydride was added to the reaction kettle, dissolved in chloroform, and 2.5 eq of amine catalyst was added. Then, 1.0 eq of silane coupling agent was added to the reaction kettle at 30 °C and reacted for 12 h. The reaction was stopped, and the mixture was washed three times with sodium hydroxide aqueous solution and three times with saturated ammonium chloride solution in sequence. The organic phase was collected and evaporated to obtain a self-water-supplying silane coupling agent.

[0055] Reactive flame retardant

[0056] In a reactor, add 1.0 eq of hydroxylamine compound and 2.0 eq of urea, stir at 80 °C for 2 h, then add 1.5 eq of itaconic anhydride and 1.5 eq of urea under a nitrogen atmosphere, stir at 140 °C for 2 h. After the reaction is completed, cool to room temperature, add deionized water to produce a white precipitate, collect the solid by filtration, wash three times with deionized water, and dry to obtain imide.

[0057] The obtained imide, halogenating agent and activating agent are dissolved in acetonitrile, stirred at 5°C for 5 min, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is slowly added, and stirring is continued for 10 min. The solid and the filtrate are filtered to obtain the solid and the filtrate. The solid is washed three times with a solvent during the filtration process, and the filtrate is then spin-dried to remove the solvent to obtain a solid product. The product is dissolved in dichloromethane, and washed three times with an aqueous sodium hydroxide solution and an aqueous hydrochloric acid solution in sequence. The organic phase is collected and spin-dried again to obtain a reactive flame retardant.

[0058] The following is the test method of the performance parameters involved in the present invention:

[0059] (1) NMR data: 400 MHz NMR instrument (Bruker, Germany);

[0060] (2) Gel content: Use a Soxhlet extractor to test the gel content of PEX-b according to the standard of GB / T17219-1998. Weigh (0.5±0.05) g of the cross-linked product, wrap it in a 100-mesh copper mesh, and then put it into a Soxhlet extractor with xylene as the solvent, boil and reflux for 10 hours, take out the sample package, and then place the sample in an 80 ℃ oven to dry for 10 hours, cool it to room temperature, and then weigh and calculate;

[0061] (3) Tensile strength: The extruder was changed to a die with a 0.5 mm sheet, and the test was carried out according to GB / T 2951.11-2008 “General test methods for insulation and sheath materials of electric and optical cables”;

[0062] (4) Elongation at break: The extruder die is 0.5 mm sheet, measured according to GB / T 2951.11-2008 “General test methods for insulation and sheathing materials of electric and optical cables”;

[0063] (5) Limiting oxygen index (LOI): The test method follows GB / T2406-2008, and the test sample size is 100 mm × 6.5 mm × 3 mm;

[0064] (6) Thermal stability test: Using a thermogravimetric analyzer, the sample was heated from room temperature to 700 °C at a heating rate of 10 °C / min;

[0065] (7) Vertical combustion grade: Determined by GB / T 8332-2008 "Test method for combustion performance of foam plastics - Horizontal combustion method" GB / T 8332-2008, the standard is UL-94, and the sample size is 100 mm × 13 mm × 3 mm.

[0066] A method for preparing a self-crosslinking high-performance flame-retardant cable comprises the following steps:

[0067] 1) Dissolve the initiator in the self-water-supply silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into an oven at 80°C for 12 hours, and then divide them into two equal parts, one part is mixed with the initiator, the self-water-supply silane coupling agent, the flame retardant and the reactive flame retardant, and the other part is mixed with the antioxidant and the catalyst, and they are placed in sealed containers and left to stand for 24 hours, and then extruded by a twin-screw extruder in turn to obtain mixed masterbatch;

[0068] 2) Add the mixed masterbatch into the preheated single screw extruder, extrude the material onto the insulating core, cool it in a water bath, place the obtained material in a humid environment at room temperature for 3 days, complete the self-crosslinking process of polyethylene, and then dry it to obtain a self-crosslinked high-performance flame-retardant cable.

[0069] Table 1 Self-crosslinking high performance flame retardant cable formula, Examples 1 to 7 (mass / kg)

[0070]

[0071] Comparative Examples 1 to 6

[0072] Same as Example 4 preparation method

[0073] Comparative Example 7

[0074] Compared with the preparation method of Example 4, the difference is that step 2) is replaced by adding the mixed masterbatch into a preheated single-screw extruder, extruding the material onto the insulating core, cooling it in a water bath, placing the resulting material in 80°C water, cooking it for 10 h, completing the cross-linking process of the polyethylene, and drying it to obtain a cross-linked high-performance flame-retardant cable.

[0075] Table 2 Self-crosslinking high performance flame retardant cable formula, comparative examples 1 to 7 (mass / kg)

[0076]

[0077] Table 3 Performance test of self-crosslinking high performance flame retardant cable

[0078]

[0079] It can be seen from the data in Table 3 that the self-crosslinking high-performance flame-retardant cables prepared in Examples 1 to 7 have a tensile strength greater than 15 MPa, an elongation at break greater than 650%, and a vertical burning grade of UL-94 standard V-0.

[0080] It can be seen from the data of Comparative Examples 1 to 4 that the comprehensive performance of the self-supply water coupling agent and the reactive flame retardant is good within a certain range; it can be seen from the data of Comparative Example 5 that when an unmodified silane coupling agent is used, the gel content is low at room temperature, and the physical properties of the prepared cable are poor; it can be seen from the data of Comparative Example 6 that the flame retardant performance of the cable prepared by using unmodified DOPO is poor; it can be seen from the data of Comparative Example 7 that the cable obtained by steaming has a high gel content and a high tensile strength, but poor elongation at break and flame retardant performance.

[0081] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A self-crosslinking high-performance flame-retardant cable, consisting of an insulating core and a flame-retardant protective sheath, characterized in that: The flame retardant protective cover comprises, by weight: 45-55 parts of linear low-density polyethylene, 15-25 parts of ethylene-octene elastomer, 1.8-2.2 parts of self-watering silane coupling agent, 10-16 parts of flame retardant, 4-8 parts of reactive flame retardant, 0.18-0.22 parts of initiator, 0.5-0.8 parts of antioxidant, and 1.6-2.2 parts of catalyst; The self-water-supply type silane coupling agent is prepared by the following method: Under a nitrogen atmosphere, 1.1-1.3 eq of itaconic anhydride is added to a reaction kettle, dissolved in chloroform, 2.5-3.0 eq of an amine catalyst is added, and 1.0 eq of a silane coupling agent is added to the reaction kettle at 25-35 °C for 8-16 h, the reaction is stopped, and the mixture is washed three times with an aqueous sodium hydroxide solution and three times with a saturated ammonium chloride solution in sequence, the organic phase is collected, and evaporated to obtain a self-water-supply type silane coupling agent; the silane coupling agent is at least one of 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane; The reactive flame retardant is prepared by the following method: S1. Synthesis of imide: In a reaction kettle, add 1.0-1.2 eq of hydroxylamine compound and 2.0-2.5 eq of urea, stir at 75-85 °C for 1-2 h, then add 1.5-1.8 eq of itaconic anhydride and 1.5-1.8 eq of urea under nitrogen atmosphere, stir at 135-145 °C for 1-2 h, cool to room temperature after the reaction, add deionized water to produce a white precipitate, collect the solid by filtration, wash with deionized water 3 times, and dry to obtain imide; S2. Synthesis of reactive flame retardant: dissolve the imide, halogenating agent and activating agent obtained in S1 with a solvent, stir for 1 to 5 min at 0 to 25 °C, slowly add 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, continue stirring for 2 to 30 min, filter to obtain a solid and a filtrate, wash the solid three times with a solvent during the filtration process, then spin-dry the filtrate to remove the solvent to obtain a solid product, dissolve the product in dichloromethane, wash three times with an aqueous sodium hydroxide solution and an aqueous hydrochloric acid solution in sequence, collect the organic phase, and spin-dry again to obtain a reactive flame retardant; The method for preparing the self-crosslinking high-performance flame-retardant cable comprises the following steps: 1) Dissolve the initiator in the self-water-supply silane coupling agent, put the linear low-density polyethylene and ethylene-octene elastomer into a 70-90 ℃ oven and dry them for 10-12 hours, then divide them into two equal parts, one part is mixed with the initiator, the self-water-supply silane coupling agent, the flame retardant and the reactive flame retardant, and the other part is mixed with the antioxidant and the catalyst, and put them into sealed containers respectively and let them stand for 18-24 hours, and extrude them respectively with a twin-screw extruder in turn to obtain mixed masterbatch; 2) Add the mixed masterbatch into the preheated single screw extruder, extrude the material onto the insulating core, cool it in a water bath, place the obtained material in a humid environment at room temperature for 2 to 3 days, complete the self-crosslinking process of polyethylene, and then dry it to obtain a self-crosslinking high-performance flame-retardant cable.

2. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The flame retardant is expandable graphite; the initiator is dicumyl peroxide; and the catalyst is dibutyltin dilaurate.

3. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The amine catalyst is at least one of triethylamine and N,N-diisopropylethylamine.

4. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The hydroxylamine compound in step S1 is at least one of choline chloride and choline bromide.

5. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The halogenating agent in step S2 is one or more of N-chlorosuccinimide, N-bromosuccinimide, N-iodosuccinimide and dibromohydantoin.

6. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The activating agent in step S2 is one or more of 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1,5-diazabicyclo[4.3.0]non-5-ene, triethylenediamine, triethylamine, triphenylphosphine and 1,8-diazabicyclo[5.4.0]undec-7-ene.

7. The self-crosslinking high-performance flame-retardant cable according to claim 1, characterized in that: The solvent in step S2 is one or more of N,N-dimethylformamide, tetrahydrofuran, toluene, dichloromethane and acetonitrile.

Citation Information

Patent Citations

  • A synergistic flame-retardant thermoplastic resin and its preparation method

    CN102276907A

  • Silane coupling agent and preparation method and application thereof

    CN111518127A